PENGARUH FINGER PAINTING TERHADAP KEMAMPUAN MENGENAL WARNA ANAK USIA DINI 4-5 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL 05 MEDAN - Diva Amalia; May Sari Lubis (STKIP Subang, 2026)
The focus of this study is the effect of finger painting on the color recognition ability of 4-5 year old children at Aisyiyah Bustanul Athfal 05 kindergarten Medan. Color recognition abilities include, such as, naming, grouping, and pointing colors. This study uses numbers to analyze data, the method used is an experiment where one group is tested before and after the experiment. 15 children were selected using a saturated sampling technique. Children’s color recognition abilities were assessed using a special observation sheet designed to obtain information, and collected through observation by observing children’s performance using a structured observation sheet aimed at assessing color recognition abilities. For the pretest, the Shapiro-Wilk normality test produced a significance value of 0.262, and 0.362 for the posttest. This indicates that the collected data is normally distributed. Furthermore, the results of the Wilcoxon Signed Rank Test showed a significance nya value of 0.001, which is lower than the 0.05 limit. Therefore, from these findings, the results of finger painting activities significantly affect children’s ability to recognize colors.